2003
DOI: 10.1152/ajprenal.00376.2002
|View full text |Cite
|
Sign up to set email alerts
|

Heme activates the heme oxygenase-1 gene in renal epithelial cells by stabilizing Nrf2

Abstract: The mechanism of heme oxygenase-1 gene ( ho-1) activation by heme in immortalized rat proximal tubular epithelial cells was examined. Analysis of the ho-1promoter identified the heme-responsive sequences as the stress-response element (StRE), multiple copies of which are present in two enhancer regions, E1 and E2. Electrophoretic mobility shift assays identified Nrf2, MafG, ATF3, and Jun and Fos family members as StRE-binding proteins; binding of Nrf2, MafG, and ATF3 was increased in response to heme. Dominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
97
1
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 154 publications
(108 citation statements)
references
References 51 publications
8
97
1
2
Order By: Relevance
“…It has been shown that activation of the ERK pathway may be required for Nrf2 nuclear translocation [43]. Nrf2 is a transcription factor that is part of the StRE and EpRE binding complexes, which may also be involved in HO-1 gene regulation [31,44,45]. No change in total EpRE binding was observed after treatment with HNE (data not shown).…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…It has been shown that activation of the ERK pathway may be required for Nrf2 nuclear translocation [43]. Nrf2 is a transcription factor that is part of the StRE and EpRE binding complexes, which may also be involved in HO-1 gene regulation [31,44,45]. No change in total EpRE binding was observed after treatment with HNE (data not shown).…”
Section: Resultsmentioning
confidence: 92%
“…c-Jun can form part of the AP-1, StRE [31], and EpRE binding complexes [64] and further, StRE-and EpRE-mediated induction of HO-1 has been shown previously in rat cell lines [31,64,65]. Although no change in total EpRE binding was observed in response to HNE, the EpRE and/ or StRE enhancer elements could still be involved in the increase in HO-1 mRNA via transcription factor complex remodeling [39], specifically through activated c-Jun joining the complex and potentially displacing an inhibitor [66].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations